An Exploratory Study of Investigating the Creative Potential of Taiwanese Children - Tsai, Kuan Chen (Journal of Educational, Health and Community Psychology, 2014)
AbstractThe question of whether creativity should be viewed as domain-general or domain-specific, and unidimensional or multidimensional, have led to a vibrant discussion among students of creativity. Following a reviewing of the relevant literature, it was decided that the present study would focus its investigation of the creative potential of Taiwanese students on verbal and visual creative abilities. Three major findings were found: first, that the relationship between verbal and visual creativity was moderate and significant, while the relationship between ideational behavior, on the one hand, and verbal creativity and visual creativity, on the other, was weak and non-significant. Second, as illustrated by our perceptual map, it appears that verbal and visual creativity are different constructs, which might tend to support the domain-specific theory of creativity. Finally, gender did not function as a moderator between verbal and visual creativity.                                                                                                      Keywords: Creativity; Visual creativity; Verbal creativity; Ideational behavior; Taiwanese children